Uji Aktivitas Daun Salam (Sizygium poyantha) Sebagai Antihipertensi Pada Tikus Jantan Yang Diinduksi Angiotensin II - oentari, octaviana dyah (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2025)
Bay leaves are one of the plants that can be used for hypertension. Matoa leaves are thought to have hypertensive activity because they contain flavonoids. Flavonoids can lower blood pressure modulated by the Renin-Angiotensin-Aldosterone System (RAAS). The purpose of this study was to determine the administration of bay leaf extracts and fractions in lowering blood pressure. This study used a maceration method with 96% ethanol solvent and fractionated with a liquid-liquid method using n-hexane fraction solvent, ethyl acetate fraction, water fraction. In this study, 21 male white rats of the Wistar strain were used as test animals divided into 7 groups. All groups except the normal group were induced with Angiotensin II. The antihypertensive activity of bay leaf extracts and fractions was observed from the percentage decrease in systolic and diastolic blood pressure. The results showed that bay leaf extract at a dose of 300 mg/kg BW could lower blood pressure in rats induced by angiotensin II.